Hospital-based screening to detect patients with cadmium nephropathy in cadmium-polluted areas in Japan - Toru Sasaki; Hyogo Horiguchi; Akira Arakawa; Etsuko Oguma; Atsushi Komatsuda; Kenichi Sawada; Katsuyuki Murata; Kazuhito Yokoyama; Takehisa Matsukawa; Momoko Chiba; Yuki Omori; Norihiro Kamikomaki (Environmental Health and Preventive Medicine, 2019)
Abstract Background In health examinations for local inhabitants in cadmium-polluted areas, only healthy people are investigated, suggesting that patients with severe cadmium nephropathy or itai-itai disease may be overlooked. Therefore, we performed hospital-based screening to detect patients with cadmium nephropathy in two core medical institutes in cadmium-polluted areas in Akita prefecture, Japan. Methods Subjects for this screening were selected from patients aged 60 years or older with elevated serum creatinine levels and no definite renal diseases. We enrolled 35 subjects from a hospital in Odate city and 22 from a clinic in Kosaka town. Urinary ß2-microglobulin and blood and urinary cadmium levels were measured. Results The criteria for renal tubular dysfunction and the over-accumulation of cadmium were set as a urinary ß2-microglobulin level higher than 10,000 μg/g cr. and a blood cadmium level higher than 6 μg/L or urinary cadmium level higher than 10 μg/g cr., respectively. Subjects who fulfilled both criteria were diagnosed with cadmium nephropathy. Six out of 57 patients (10.5% of all subjects) had cadmium nephropathy. Conclusions This hospital-based screening is a very effective strategy for detecting patients with cadmium nephropathy in cadmium-polluted areas, playing a complementary role in health examinations for local inhabitants. Registration number No. 6, date of registration: 6 June, 2010 (Akita Rosai Hospital), and No. 1117, date of registration: 26 December, 2013 (Akita University).